Consortium of endophyte and rhizosphere phosphate solubilizing bacteria improves phosphorous use efficiency in wheat cultivars in phosphorus deficient soils - Emami, Somayeh; Alikhani, Hossein Ali; Pourbabaee, Ahmad Ali; Etesami, Hassan; Motasharezadeh, Babak; Sarmadian, Fereydoon (Rhizosphere, 2020)
Rhizospheric and endophytic bacteria are known to increase phosphorus efficiency (PE) of plant in phosphorus-deficient soils. The purpose of this research was to examine the role of rhizospheric and endophytic bacterial inoculation in increasing phosphorus acquisition efficiency (PAE) and phosphorus utilization efficiency (PUE) by solubilization of phosphate and expanding of root system. A total of 22 isolates were selected from rhizosphere and inside root of wheat (Triticum aestivum L.) plants based on plant growth promoting traits. These isolates significantly solubilized phosphorus from tri-calcium phosphate and produced indole-3-acetic acid (IAA) under in vitro condition. In pot experiment, we found that rhizospheric and endophytic bacterial inoculation improved root and shoot dry matter, grain yield, length, surface area and volume of roots. At the ripening stage, the consortium treated (co-inoculation with rhizospheric and endophytic bacteria) pots exhibited enhanced the plant height (up to 15.0% and 11.0%), shoot dry weight (up to 5.8% and 7.5%), root dry weight (up to 68% and 58%) and grain yield (up to 58.0% and 42.0%), in Marvdasht and Roshan cultivars respectively. The uptake of P was 3.61 mg pot−1 for Marvdasht cultivar and 6.44 mg pot−1 for Roshan cultivar. Inoculation with rhizospheric isolate increased PE index by 29.5% and 18.7% in Marvdasht and Roshan cultivars, respectively. Noticeable effect was detected in case of consortium treatment, suggesting that plant growth promoting rhizobacteria acted synergistically with plant growth promoting endophytes. Finally, our study highlights the importance of co-inoculation with rhizospheric and endophytic bacterial inoculant in improving P efficiency of wheat cultivars. •This is the first paper to report that phosphate-solubilizing bacteria (PSB) were increased phosphorus efficiency of plant.•Inoculation increased phosphorus acquisition efficiency by increasing phosphorus uptake from soils.•Phosphate solubilizing rhizobacteria acted synergistically with phosphate solubilizing endophytes.•The PSB improved the root growth indices and grain yield.